Upaya Guru terhadap Pengembangan Aspek Bahasa Anak Usia Dini Melalui Film Nussa dan Rara - Yunanda, BRE (Institut Agama Islam Sumatera Barat Pariaman, 2023)
The aim of this research is to develop aspects of early childhood language through the film Nussa and Rara. This research uses qualitative methods. The results of the study can be concluded that the Nussa and Rara films can also be used by parents and educators, because apart from being able to develop children's language, these films also direct children to optimize social-emotional traits so that children have a sense of empathy and care for one another and also teaches children to know the value of religious character, honest character, creative character, curiosity character, national spirit character, and responsibility character value. The process of implementing children's language development through the Nussa and Rara film method at the Wiyata Putra KB can run effectively with the teacher mastering the material to be delivered to children, giving directions and steps during the screening of the Nusa and Rara films, so that the purpose of the learning process is to improve children's language development. goes well.